Idiopathic calcinosis cutis of the right iliac region: Common lesion at uncommon - Gaffoor, Nidha; Edupuganti, Hima Sree; Minal, Jessica; Shetty, Archana; T R, Supriya; Muralidhar, Aparna (Indian Journal of Case Reports, 2021)
Calcinosis cutis is an uncommon soft tissue lesion characterized by the deposition of calcium salts in the skin or subcutaneous tissue attributed to a wide variety of causes. We present a case of idiopathic calcinosis cutis in an adult male, who presented with a swelling in the right iliac region. Chalky white aspirate and amorphous basophilic granular material on microscopy suggestive of calcium deposits were noted. Histopathological examination of the excised mass coupled with appropriate clinical background led to the final diagnosis of idiopathic calcinosis cutis. We present this case with a complete diagnostic workup to undermine the importance of considering this lesion in the differential diagnoses of a subcutaneous hard lump in an otherwise healthy patient.